Uji Validitas Konstruk Work Role Performance pada Karyawan di Indonesia - Bella Saviera; Hery Susanto; Anissa Lestari Kadiyono (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
Employee performance is critical to the overall success of the company. In achieving their goals, companies will face many challenges. This can be overcome in several ways, one of which is by improving employee performance. Therefore, it is important to measure the role performance of employee in Indonesia. Work role performance scale was first delevoped in Australia in 2007 and have not been adapted for Indonesian population. This study intends to evaluate the validity and the reliability of the Indonesian version of work role performance scale. Aiken’s V formula was used to evaluate the content validity of the scale. Both CTT and Rasch analysis were employed to evaluate the reliability of the scale. Participants in this study were employees, with a total of 370 (n = 370), collected by using accidental sampling techniques. The results showed Aiken’s V of 0.87 to 0.91 shows that items of the adapted scale were relevant to measure the construct. The adapted scale was found reliable with Cronbach’s alpha of 0.936 and Rasch’s person and item reliability were 0.87 and 0.98. In CFA results, the model fit was acceptable (RMSEA=0.08 and CFI=0.96) shows that the data fit the hypoteshized model.